2013
DOI: 10.1038/nature12268
|View full text |Cite
|
Sign up to set email alerts
|

North Atlantic Ocean control on surface heat flux on multidecadal timescales

Abstract: Nearly 50 years ago Bjerknes suggested that the character of large-scale air-sea interaction over the mid-latitude North Atlantic Ocean differs with timescales: the atmosphere was thought to drive directly most short-term--interannual--sea surface temperature (SST) variability, and the ocean to contribute significantly to long-term--multidecadal--SST and potentially atmospheric variability. Although the conjecture for short timescales is well accepted, understanding Atlantic multidecadal variability (AMV) of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

45
241
1
4

Year Published

2014
2014
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 273 publications
(291 citation statements)
references
References 31 publications
(42 reference statements)
45
241
1
4
Order By: Relevance
“…12, bottom row panels), the correlation is positive almost all over the small basin. At those timescales, ocean-atmosphere heat fluxes are mainly driven by the atmosphere, consistent with the stochastic forcing of the ocean in the Frankignoul and Hasselmann (1977)'s paradigm, and the results of Gulev et al (2013). However, a negative correlation is observed along the western boundary of the subpolar gyre, and spreads over a wider region as the resolution increases.…”
Section: Air-sea Heat Fluxessupporting
confidence: 77%
See 2 more Smart Citations
“…12, bottom row panels), the correlation is positive almost all over the small basin. At those timescales, ocean-atmosphere heat fluxes are mainly driven by the atmosphere, consistent with the stochastic forcing of the ocean in the Frankignoul and Hasselmann (1977)'s paradigm, and the results of Gulev et al (2013). However, a negative correlation is observed along the western boundary of the subpolar gyre, and spreads over a wider region as the resolution increases.…”
Section: Air-sea Heat Fluxessupporting
confidence: 77%
“…Using observational data, Gulev et al (2013) have confirmed the Bjerknes (1964) assumption for the North Atlantic sector: Q ′ is driven by ocean dynamics on long-term (multidecadal timescales), but by the atmospheric dynamics on short-term (interannual to decadal timescales). To investigate this issue in our model, we compute now the short-term signal by taking the deviation from the longterm signal, i.e.…”
Section: Air-sea Heat Fluxessupporting
confidence: 61%
See 1 more Smart Citation
“…Figure 7a shows the upward surface heat flux anomalies in association with the NAT. The heat flux anomaly has a similar pattern to the NAT, reflecting that the atmosphere acts to damp the SST anomalies over multidecadal timescales (Gulev et al 2013). As a result, the low-level air temperature is affected and shows anomalous cooling and warming in the subpolar and subtropical basins, respectively (Fig.…”
Section: Possible Mechanisms Involvedmentioning
confidence: 79%
“…The dominant role of heat transport convergence in driving long-term OHC changes in the North Atlantic was also deduced through comprehensive analyses of ORA models [26,73]. These multi-decadal OHC changes exert a strong influence on surface temperature patterns such as the Atlantic Multi-decadal Oscillation [11], which subsequently drive turbulent heat fluxes at the air-sea interface and associated atmospheric responses [24].…”
Section: Observational Insights Into the Regional Dynamics: An Atlantmentioning
confidence: 99%